The importance and problems of applying the requirements of the International Audit Standards (ISA) in the private banks operating in the Kurdistan Region - Exploratory study - Ghazi O. Mahmood (Zanco Journal of Humanity Sciences)
The aim of this research is to shed light on the importance and importance of international auditing standards, and to know the problems of applying these standards in full in the institutions of civil banks in the Kurdistan Region - Iraq and identify ways to address these problems, in addition to the importance of applying the international audit standards in the scope of this audit The institutions by which the auditor moves to reach the final conclusion about expressing his or her opinion. The research is based on the main hypothesis that civil institutions and banks in the Kurdistan Region - Iraq do not face problems in applying the requirements of international auditing standards and not fully applying these standards,In order to achieve the objectives of the research, a descriptive and inductive approach was adopted to study the success of banks and to design a questionnaire addressed to specialists from academics and professionals (accountants and auditors), to survey their opinions regarding aspects of research and testing hypotheses. As an inevitable consequence of the globalization of business, the demise of geographical boundaries, the emergence of multinational corporations and their increasing role in international relations, it helps to overcome some of the barriers to international transactions. The research has come up with several recommendations, the most important of which are to reduce the disparity in performance among practitioners and to obtain credible financial information at the international level. It is also necessary to introduce the curriculum and standards of international auditing in accounting and auditing education in universities and institutes, as well as to focus on the quality of graduates and attention to field training better than it is now.